2021
DOI: 10.1249/mss.0000000000002810
|View full text |Cite
|
Sign up to set email alerts
|

Are Gait Biomechanics Related to Physical Activity Engagement? An Examination of Adolescents with Autism Spectrum Disorder

Abstract: PurposeAdolescents with autism spectrum disorder (ASD) rarely meet physical activity (PA) guidelines, thus not reaping associated health benefits. Although many barriers exist, abnormal or inefficient gait biomechanics could negatively impact engagement in PA. This study has two purposes: first, to compare total body mechanical work between adolescents with ASD and neurotypical age-, sex-, and body mass index–matched controls, and second to determine whether gait biomechanics are significantly related to engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Three articles, identified via a manual snowball search, also met the inclusion criteria. Finally, 28 studies were selected for systematic review and meta-analysis as the data was considered sufficient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three articles, identified via a manual snowball search, also met the inclusion criteria. Finally, 28 studies were selected for systematic review and meta-analysis as the data was considered sufficient.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles, identified via a manual snowball search, also met the inclusion criteria. Finally, 28 studies 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 were selected for systematic review and meta-analysis as the data was considered sufficient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While physical activity is essential for healthy development [ 3 ] during adolescence, the practice of walking has become less common in modern societies [ 4 ]. This is concerning as research has demonstrated that regular physical activity, including walking, can have significant physiological and psychological benefits for adolescents [ 5 , 6 ]. Therefore, it is crucial to understand the impact of walking on the developing adolescent brain and its potential role in promoting healthy brain development.…”
Section: Introductionmentioning
confidence: 99%